Comparing cybersickness in virtual reality and mixed reality head-mounted displays - Kirollos, Ramy; Merchant, Wasim (Frontiers in Virtual Reality, 2023)
Introduction: Defence Research and Development Canada is developing guidance on the use of Mixed Reality head-mounted displays for naval operations in the Royal Canadian Navy. Virtual reality head-mounted displays display graphics to the user in 3D and completely occlude the user’s view of the real world. Mixed Reality head-mounted displays overlay and integrate graphics onto the real world allowing the user to perceive the real world and rich 3D graphic elements simultaneously. Nausea and other debilitating symptoms caused by the use of head-mounted displays, known as ‘cybersickness’, is well documented during Virtual reality head-mounted display exposure and can be quite severe. However, it is not yet clear from the literature on Mixed Reality head-mounted displays whether CS differs in Virtual reality vs. Mixed Reality head-mounted displays. The objective of this study was to determine the impact of MR HMDs on CS. Method: This was done by modulating the quantity of graphics in two Mixed Reality conditions and one Virtual reality condition. Only foreground objects were graphically rendered in the first Mixed Reality condition (called ‘Mixed Reality’ condition), while the entire scene was graphically rendered in the second Mixed Reality condition (called ‘Mixed Reality +’ condition). The Virtual reality condition simulated the Mixed Reality + condition but was displayed in a Virtual reality head-mounted display. Participants observed the virtually rendered scene in one of the three conditions and reported their CS with the simulator sickness questionnaire six times throughout the 30-min experiment. We hypothesized that CS severity would increase as quantity of graphics in the display increased. Results and Discussion: Findings indicated that CS was significantly greater in the ‘Mixed Reality +’ condition compared to the ‘Mixed Reality’ and ‘Virtual reality’ conditions, providing partial evidence for our main hypothesis. Moreover, CS increased significantly and meaningfully after 25 min in the ‘Mixed Reality +’ condition. These findings indicate safe use of Mixed Reality head-mounted displays by the RCN for shore-based applications provided quantity of graphics is limited.